A 2-in-1 multi-functional sensor for efficient epinephrine detection based on a cucurbit[7]uril functionalized lanthanide metal–organic framework and its intelligent application in a molecular robot. Issue 24 (10th June 2022) - Zhang, Yu; Yan, Bing
Abstract : The immediate identification of disease analytes in the human body requires a facile sensing method with high reliability and selectivity. Abstract : The immediate identification of disease analytes in the human body requires a facile sensing method with high reliability and selectivity. Therefore, developing a multifunctional sensor with both enrichment ability and sensing function is of great significance for the high-precision monitoring of disease analytes. Herein, a 2-in-1 multifunctional optical sensor (CB@CH3 -TbMOF, where CB = cucurbit[7]uril and TbMOF = terbium metal–organic framework) for serum epinephrine (EPI) detection was fabricated via the assembly of CB and a fluorescent TbMOF through the formation of a donor–acceptor (D–A) composite between CB and the N-methylated TbMOF (CH3 -TbMOF). In this EPI sensing system, Tb 3+ as a fluorescent signal reporter can provide an obvious and visual fluorescence response during EPI sensing, while CB as an enriching element can capture the surrounding EPI by the electrostatic interactions between the carbonyl portals of the CB and the protonated amine groups of EPI, which effectively improves the sensitivity and precision of the sensor. In view of the high sensitivity of the sensor and the visualization of the sensing results, we further explored the intelligent molecular robot application of the EPI sensing process. After grasping the molecular signals of the actuator (CB), the molecular robot is supposed to react autonomously to EPI via sensors (fluorescence of Tb 3+ ) and then make decisions via a processor with computation (tandem combinational logic gates), finally precisely outputting the concentration of EPI. This work provides a new approach for developing a 2-in-1 multifunctional EPI sensor with both enrichment ability and sensing function. What is more, this work represents the first effort made toward identifying EPI in serum using a fluorescent intelligent molecular robot.